Manufacturing method of cylindrical concrete pile
Patent Information
- Application Number
- JP2023128985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-21
Smart Images

Figure 2025024750000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a cylindrical concrete pile. [Background technology]
[0002] The mainstream construction method using bearing piles is the high-bearing-capacity method using bearing piles with a tip bearing capacity coefficient α of 250 or more, but in recent years, construction methods using bearing piles with a tip bearing capacity coefficient α of over 1,000 have also been developed. The mainstream design strength of concrete used for prefabricated bearing piles is 80 to 105 N / mm 2 However, in order to increase the tip bearing capacity coefficient α of a bearing pile using concrete with the above design standard strength (for example, to exceed 600), it is necessary to increase the thickness of the bearing pile. However, when the thickness is increased, problems such as an increase in excavation surplus soil and an increase in the logistics costs of the bearing pile arise. For this reason, there is a demand for high-strength concrete that can be used to manufacture a bearing pile with a higher tip bearing capacity coefficient α while maintaining the thickness of the bearing pile.
[0003] As a method for manufacturing a centrifugally molded concrete pipe having excellent compressive strength, Patent Document 1 describes a method for manufacturing a high-strength centrifugally molded concrete pipe, in which water is added to coarse aggregate, fine aggregate, fine-grained admixture for high strength, water-reducing agent, and cement, the mixture is kneaded, and centrifugally molded to form a concrete pipe. In this method, the total powder weight of the cement or the cement and fine-grained admixture is 650 kg / m 3 The above describes a method for producing a high-strength centrifugally molded concrete pipe, characterized in that the ratio of water to the total powder weight (water-powder ratio) is 21% by weight or less, the ratio of fine aggregate volume to total aggregate volume (fine aggregate ratio s / a) is 45% or less, the paste fine aggregate ratio α indicating the filling rate of the fine aggregate voids in the cement paste is 2.0<α<3.0, and the mortar coarse aggregate ratio β indicating the filling rate of the coarse aggregate voids in the mortar is 2.5<β<3.6, and by adjusting the amount of the water reducing agent added, the slump flow value is set to 400mm to 800mm and the 50cm slump flow time is set to 15 seconds or more. In addition, as a pile made of a material having high compressive strength, Patent Document 2 discloses a pile made of a cementitious hardened body, in which the cementitious hardened body is made of cement, and has a BET specific surface area of 15 to 25 m 2 The document describes a pile characterized in that it is a hardened product of a cement composition comprising: silica fume of 0.1 to 1.5 g / g; inorganic powder having a 50% volume cumulative particle size of 0.8 to 5 μm; aggregate A having a maximum particle size of 1.2 mm or less; a high-performance water-reducing agent; an antifoaming agent; and water, wherein the cement accounts for 55 to 65 volume % of the cement, the silica fume for 5 to 25 volume % of the silica fume, and the inorganic powder for 100 volume % in total. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-32246 A [Patent Document 2] JP 2017-95914 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a method for producing a cylindrical concrete pile having excellent formability and high compressive strength. [Means for solving the problem]
[0006] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned objects can be achieved by a production method comprising the steps of: supplying a cement composition containing cement, silica fume, inorganic powder, fine aggregate, coarse aggregate, a cement dispersant, and water into a formwork for centrifugal molding, and then centrifugally molding while vibrating the formwork; sealing and curing the unhardened green body and then removing it from the formwork; and steam curing the cylindrical green body to obtain a cylindrical concrete pile, wherein, out of a total of 100 volume % of cement, silica fume, and inorganic powder, the proportion of cement is 55 to 65 volume %, the proportion of silica fume is 5 to 25 volume %, the proportion of inorganic powder is 15 to 35 volume %, (water / (total of cement, silica fume, and inorganic powder)) is 0.11 to 0.16, and the proportion of coarse aggregate in the cement composition is 15 to 40 volume %, and have completed the present invention. That is, the present invention provides the following [1] to [7]. [1] Cement and a BET surface area of 15 to 25 m 2 a forming step of supplying a cement composition containing silica fume having a particle size of 0.8 to 5 μm, fine aggregate, coarse aggregate, a cement dispersant, and water to a form for centrifugal molding, and then centrifugally molding the cement composition while vibrating the form to obtain an unhardened cylindrical green body; a room temperature curing step of subjecting the unhardened cylindrical green body to sealed curing or air curing at 10 to 40° C. for 20 hours or more, and then removing the unhardened cylindrical green body from the form to obtain a hardened cylindrical green body; and a steam curing step of subjecting the hardened cylindrical green body to steam curing at 70° C. or more and less than 100° C. for 12 hours or more to obtain a cylindrical concrete pile. and a steam curing step of obtaining a cement composition having a ratio of 55 to 65 volume %, 5 to 25 volume % of the silica fume, and 15 to 35 volume % of the inorganic powder, based on a total amount of 100 volume % of the cement, the silica fume, and the inorganic powder, a mass ratio of the water to the total of the cement, the silica fume, and the inorganic powder (water / (total of the cement, the silica fume, and the inorganic powder)) is 0.11 to 0.16, and a ratio of the coarse aggregate in the cement composition is 15 to 40 volume %.
[0007] [2] A method for manufacturing a cylindrical concrete pile as described in [1], wherein the formwork has a plurality of annular convex portions provided on the outer periphery of the formwork, and in the molding process, while the formwork is rotated around an axis along the longitudinal direction of the formwork, a vibration means for applying vibration to the formwork is arranged vertically below at least one of the annular convex portions, and vertical vibration is applied to the formwork via the annular convex portions. [3] A method for manufacturing a cylindrical concrete pile as described in [2], wherein in the molding process, the formwork is vibrated while rotating it around its longitudinal axis at a centrifugal acceleration of 10 G or less. [4] The method for manufacturing a cylindrical concrete pile according to any one of [1] to [3], wherein the maximum particle size of the coarse aggregate is 10 to 25 mm. [5] The compressive strength of the cylindrical concrete pile, measured in accordance with "JIS A 1136:2018 (Test method for compressive strength of centrifugally compacted concrete)", is 175 N / mm 2 The method for manufacturing a cylindrical concrete pile according to any one of [1] to [4] above. [6] The method for manufacturing a cylindrical concrete pile according to any one of [1] to [5], wherein the cylindrical concrete pile has a thickness of 30 to 300 mm, half of the value obtained by subtracting the inner diameter from the outer diameter. [7] The method for manufacturing a cylindrical concrete pile according to any one of [1] to [6], wherein the cylindrical concrete pile has an outer diameter of 150 to 3,000 mm. Effect of the Invention
[0008] According to the manufacturing method of the cylindrical concrete pile of the present invention, a cylindrical concrete pile having excellent formability during centrifugal molding and high compressive strength can be manufactured. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a longitudinal side view of an example of a vibration centrifugal molding device used in the present invention. [Diagram 2]FIG. 2 is a front view of an example of a vibration centrifugal molding apparatus used in the present invention, taken in a direction perpendicular to the longitudinal direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The method for manufacturing a cylindrical concrete pile of the present invention comprises the steps of: 2 The present invention relates to a cement composition comprising silica fume having a particle size of 0.8 to 5 μm, fine aggregate, coarse aggregate, a cement dispersant, and water, which is supplied to a form for centrifugal molding, and then the form is vibrated while centrifugal molding the cement composition to obtain an unhardened cylindrical green body. The method further comprises the steps of: supplying the cement composition to a form for centrifugal molding, and then centrifugally molding the cement composition while vibrating the form to obtain an unhardened cylindrical green body; curing the unhardened cylindrical green body in a sealed state or in an air state at 10 to 40° C. for 20 hours or more, and then removing the unhardened cylindrical green body from the form for a room temperature curing step to obtain a hardened cylindrical green body; and curing the hardened cylindrical green body at a temperature of 70° C. or more and less than 100° C. for 12 hours or more. and a steam curing step for obtaining a cylindrical concrete pile by steam curing. In the cement composition, the proportion of cement is 55 to 65 volume %, the proportion of silica fume is 5 to 25 volume %, and the proportion of inorganic powder is 15 to 35 volume % out of a total of 100 volume % of cement, silica fume, and inorganic powder, the mass ratio of water to the total of cement, silica fume, and inorganic powder (water / (total of the above cement, silica fume, and inorganic powder)) is 0.11 to 0.16, and the proportion of coarse aggregate in the cement composition is 15 to 40 volume %.
[0011] Each material contained in the cement composition used in the manufacturing method of the present invention will be described in detail below. Examples of cement include various types of Portland cement such as ordinary Portland cement, high-early-strength Portland cement, ultra-high-early-strength Portland cement, moderate-heat Portland cement, sulfate-resistant Portland cement, low-heat Portland cement, etc. These may be used alone or in combination of two or more. Among these, from the viewpoint of improving the fluidity of the cement composition before hardening, moderate-heat Portland cement and low-heat Portland cement are preferred, and moderate-heat Portland cement is more preferred.
[0012] The BET specific surface area of silica fume is 15 to 25 m 2 / g, preferably 17 to 23 m 2 / g, particularly preferably 18 to 22m 2 / g. The specific surface area is 15 m 2 If the specific surface area is less than 25 m / g, the strength development of the cement composition is reduced. 2 If it exceeds 1 / g, the fluidity of the cement composition before hardening decreases.
[0013] Examples of inorganic powders having a 50% cumulative volume particle size of 0.8 to 5 μm include quartz powder (silica powder), volcanic ash, fly ash (classified or crushed), slag powder, limestone powder, feldspar powder, mullite powder, alumina powder, silica sol, carbide powder, nitride powder, crushed emery sand, etc. These may be used alone or in combination of two or more. Among these, quartz powder and fly ash are preferred from the viewpoint of improving the fluidity and strength development of the cement composition before hardening. In addition, the inorganic powder is preferably one containing SiO2 as a main component. The content of SiO2 in the inorganic powder is preferably 50 mass% or more, more preferably 60 mass% or more, and particularly preferably 70 mass% or more, from the viewpoint of further improving the strength development of the cement composition. In this specification, the inorganic powder having a 50% volume cumulative particle size of 0.8 to 5 μm does not include cement.
[0014] The 50% volume cumulative particle size of the inorganic powder is 0.8 to 5 μm, preferably 1 to 4 μm, more preferably 1.1 to 3.5 μm, and particularly preferably 1.2 μm or more and less than 3 μm. If the particle size is less than 0.8 μm, the fluidity of the cement composition before hardening decreases. If the particle size exceeds 5 μm, the strength development of the cement composition decreases. The 50% volume cumulative particle size of the inorganic powder can be determined using a commercially available particle size distribution measuring device (for example, product name "Microtrac HRA Model 9320-X100" manufactured by Nikkiso Co., Ltd.). Specifically, a particle size distribution measuring device is used to create a cumulative particle size curve, and the 50% volume cumulative particle size can be calculated from the cumulative particle size curve. 3 0.06 g of a sample is added to each of the samples, and the mixture is ultrasonically dispersed for 90 seconds using an ultrasonic dispersing device (for example, product name "US300" manufactured by Nippon Seiki Seisakusho Co., Ltd.), and then the measurement is performed.
[0015] The maximum particle size of the inorganic powder is preferably 15 μm or less, more preferably 14 μm or less, and particularly preferably 13 μm or less, from the viewpoint of improving the strength development of the cement composition. The 95% volume cumulative particle size of the inorganic powder is preferably 8 μm or less, more preferably 7 μm or less, and particularly preferably 6 μm or less, from the viewpoint of improving the strength development of the cement composition.
[0016] The cement composition contains 55 to 65% by volume of cement, silica fume, and inorganic powder in a total amount of 100% by volume, preferably 57 to 63% by volume, and more preferably 59 to 61% by volume. If the ratio is less than 55% by volume, the strength development of the cement composition decreases. If the ratio is more than 65% by volume, the fluidity of the cement composition before hardening decreases. The proportion of silica fume in the total amount of cement, silica fume and inorganic powder (100% by volume) is 5-25% by volume, preferably 7-23% by volume, and more preferably 10-20% by volume. If the proportion is less than 5% by volume, the strength development of the cement composition decreases. If the proportion is more than 25% by volume, the fluidity of the cement composition before hardening decreases. Furthermore, the ratio of the inorganic powder to the total amount of cement, silica fume and inorganic powder (100% by volume) is 15-35% by volume, preferably 17-33% by volume, and more preferably 20-30% by volume. If the ratio is less than 15% by volume, the strength development of the cement composition decreases. If the ratio is more than 35% by volume, the fluidity of the cement composition before hardening decreases.
[0017] Examples of fine aggregates include river sand, mountain sand, land sand, sea sand, crushed sand, silica sand, limestone aggregate, slag fine aggregate, lightweight fine aggregate, clinker fine aggregate, and CCU fine aggregate (fine aggregate in which carbon dioxide is fixed in one or more selected from recycled aggregate, waste concrete, blast furnace slab, and steelmaking slag), etc. These may be used alone or in combination of two or more. The proportion of fine aggregate in the cement composition is preferably 25 to 50% by volume, more preferably 30 to 45% by volume, even more preferably 32 to 42% by volume, and particularly preferably 35 to 40% by volume. If the proportion is 25% by volume or more, the fluidity of the cement composition before hardening can be improved, the heat generation amount of the cement composition can be reduced, and the shrinkage amount of a cylindrical concrete pile (hardened product of the cement composition) can be reduced. If the proportion is 50% by volume or less, the strength development of the cement composition can be further improved.
[0018] Examples of coarse aggregates include river gravel, mountain gravel, land gravel, sea gravel, crushed stone, limestone aggregate, slag coarse aggregate, lightweight coarse aggregate, clinker coarse aggregate, and CCU coarse aggregate (coarse aggregate in which carbon dioxide is fixed in one or more selected from recycled aggregate, waste concrete, blast furnace slab, and steelmaking slag), etc. These may be used alone or in combination of two or more. The maximum particle size of the coarse aggregate is preferably 10 to 25 mm, more preferably 11 to 22 mm, and particularly preferably 13 to 18 mm. If the maximum particle size is 10 mm or more, the moldability in the molding step described below is improved. If the maximum particle size is 25 mm or less, the strength development of the cement composition is improved. In this specification, the maximum particle size of aggregate (fine aggregate and coarse aggregate) refers to the particle size of the aggregate indicated by the nominal size of the smallest sieve among those through which 90% by mass or more of the total aggregate passes (this is generally known as the definition of the maximum particle size of aggregate).
[0019] The crushing value of the coarse aggregate is preferably 11% or less, more preferably 5 to 10%, and particularly preferably 6 to 9%. If the crushing value is 11% or less, the strength development of the cement composition is improved. The above-mentioned "crushing value" can be measured in accordance with the method (Methods for determination of aggregate crushing value) specified in "British Standard (BS) 812:Part 110:1990".
[0020] More specifically, the crushing value of the coarse aggregate can be measured, for example, by the following method. (1) The coarse aggregate to be measured is classified using sieves with 10 mm and 15 mm openings, and 10 kg of samples with a grain size of 10 to 15 mm are prepared. Two sets of samples are prepared. (2) The above sample is packed into a measuring container in three layers. As each layer is packed, the surface of each layer is poked 25 times with a poker from a height of approximately 50 mm, and then the surface is smoothed. (3) After transferring the sample to a container such as a tray, the sample is dried at 100 to 110°C for 4 hours and then naturally cooled to room temperature, and then the mass A of the sample is measured to the nearest 1g. (4) The above sample is packed into a test container in three layers. As each layer is packed, the surface of each layer is poked 25 times with a poker from a height of approximately 50 mm, and then the surface is smoothed. (5) Place a plunger in the test container and use a compression testing machine to load the plunger at a rate of 40 kN per minute until the compressive load reaches 400 kN, and then remove the load. (6) After classifying the sample in the test container using a sieve with 2.5 mm openings, the sample remaining on the sieve is measured to the nearest 1 g, and the mass B of the sample that passes through the 2.5 mm openings is calculated from the obtained measurement values. (7) Calculate the crushing value of the sample using the following formula (1). Crushing value (%) = (mass B / mass A) × 100 (1) (8) For each of the two samples, the above steps (2) to (7) are carried out to calculate the crushing value of the sample, and the average of the calculated crushing values is then regarded as the crushing value of the coarse aggregate.
[0021] The ratio of the coarse aggregate in the cement composition is 15 to 40% by volume, preferably 18 to 38% by volume, more preferably 21 to 30% by volume, and particularly preferably 22 to 28% by volume, from the viewpoints of improving the strength development of the cement composition and the moldability in the molding step described below. If the ratio is less than 15% by volume, the amount of heat generated by the cement composition increases, and the amount of shrinkage of the hardened body (a cylindrical concrete pile) increases.
[0022] The total amount of fine aggregate and coarse aggregate in the cement composition is preferably 50-70% by volume, more preferably 55-68% by volume, and particularly preferably 58-65% by volume. If the amount is 50% by volume or more, the amount of heat generated by the cement composition is smaller, and the amount of shrinkage of the hardened body (cylindrical concrete pile) is larger. If the amount is 70% by volume or less, the strength development of the cement composition can be further improved. The fine aggregate ratio (s / a) of the cement composition is preferably 40 to 70%, more preferably 45 to 65%, and particularly preferably 56 to 62%. If the fine aggregate ratio is within the above range, the moldability is improved in the molding step described below. The fine aggregate ratio refers to the volume ratio of fine aggregate to the total amount of fine aggregate and coarse aggregate.
[0023] Examples of the cement dispersant include lignin-based, naphthalenesulfonic acid-based, melamine-based, or polycarboxylic acid-based water reducing agents, AE water reducing agents, high-performance water reducing agents, and high-performance AE water reducing agents. These may be used alone or in combination of two or more. Among them, from the viewpoint of moldability in the molding step described below and strength development of the cement composition, high-performance water reducing agents and high-performance AE water reducing agents are preferred, and high-performance water reducing agents are more preferred. The amount of the cement dispersant is preferably 0.20 to 1.0 parts by mass, more preferably 0.30 to 0.8 parts by mass, and particularly preferably 0.40 to 0.7 parts by mass, calculated as solid content, relative to 100 parts by mass of the total amount of cement, silica fume, and inorganic powder. If the amount is 0.20 parts by mass or more, the water reducing performance is improved, and the fluidity of the cement composition before hardening is improved. If the amount is 1.0 part by mass or less, the strength development of the cement composition is improved.
[0024] The cement composition may contain a cement admixture other than the above-mentioned cement dispersant. Examples of cement admixtures other than the above-mentioned cement dispersants include antifoaming agents, AE agents, fluidizing agents, setting retarders, etc. Among them, from the viewpoint of improving the strength development of the cement composition, it is preferable that the cement composition contains an antifoaming agent. The amount of the antifoaming agent is preferably 0.001 to 0.5 parts by mass, more preferably 0.01 to 0.3 parts by mass, and particularly preferably 0.05 to 0.2 parts by mass, based on 100 parts by mass of the total amount of cement, silica fume, and inorganic powder. If the amount is 0.001 parts by mass or more, the strength development of the cement composition is improved. If the amount exceeds 0.5 parts by mass, the effect of improving the strength development of the cement composition reaches a plateau.
[0025] As the water, tap water or the like can be used. The mass ratio of water to the total of the above-mentioned cement, silica fume and inorganic powder (water / (total of cement, silica fume and inorganic powder)) is 0.11 to 0.16, preferably 0.12 to 0.15, and particularly preferably 0.13 to 0.14. If the mass ratio is less than 0.11, the moldability in the molding step described below decreases. If the mass ratio exceeds 0.16, the strength development of the cement composition decreases.
[0026] The method for producing a cylindrical concrete pile of the present invention includes a molding step of supplying the above-mentioned cement composition to a formwork for centrifugal molding, and then centrifugally molding the cement composition while vibrating the formwork to obtain an unhardened cylindrical molded body, a room temperature curing step of sealing and curing the unhardened cylindrical molded body at 10 to 40°C for 20 hours or more, and then removing it from the formwork to obtain a hardened cylindrical molded body, and a steam curing step of steam curing the hardened cylindrical molded body at 70°C or more and less than 100°C for 12 hours or more to obtain a cylindrical concrete pile (hereinafter also simply referred to as a "concrete pile"). Each step will be explained in detail below.
[0027] [Molding process] This process uses cement and a pulverized slag with a BET specific surface area of 15 to 25 m 2 The process is a process in which a cement composition containing silica fume having a particle size of 0.8 to 5 μm, inorganic powder having a 50% cumulative particle size by volume of 0.8 to 5 μm, fine aggregate, coarse aggregate, a cement dispersant, and water is supplied to a formwork for centrifugal molding, and then the cement composition is centrifugally molded while vibrating the formwork to obtain an unhardened cylindrical green body. The cement composition is usually prepared by kneading (mixing) each material constituting the cement composition in advance, and then supplying it to a form for centrifugal molding. The method of kneading each material is not particularly limited, but examples thereof include a method of kneading each material all at once, a method of mixing materials other than water and the cement dispersant, and then adding a mixture obtained by mixing water and the cement dispersant in advance to the obtained mixture and kneading it. The device used for kneading is not particularly limited, and any commonly used mixer such as an omni mixer, a pan-type mixer, a twin-shaft mixer, or a tilting mixer can be used. The cement composition may have reduced or eliminated air bubbles in the cement composition. By reducing or eliminating air bubbles in the cement composition, the strength development of the cement composition can be further improved.
[0028] The centrifugal molding method in the above molding step is a general centrifugal molding method used in the manufacture of cylindrical piles having hollow interiors, such as bearing piles, in which vibration is applied to a formwork for centrifugal molding. High-strength concrete has high viscosity and therefore requires high fluidity in order to be poured into a formwork. However, when centrifugal molding is used, such as for the manufacture of cylindrical piles, if the fluidity of the cement composition (concrete) is too high, the cement composition on the inner surface of the pile loses its shape after centrifugal molding, making molding impossible. Therefore, the concrete used for cylindrical piles is generally a hard concrete with a slump of 10 cm or less, but the concrete with a slump of 175 N / mm 2 Concrete that achieves this level of strength has an extremely high viscosity, so even if centrifugal molding is performed, the concrete may not fill the formwork sufficiently, and problems with moldability may arise, such as the concrete not forming a uniform cylindrical shape. In order to solve these problems, the moldability can be improved by applying vibration during centrifugal molding (specifically, by vibrating the mold frame). Hereinafter, an example of a mold for centrifugal molding and a vibration centrifugal molding machine used in the production method of the present invention will be described with reference to Figs. 1 and 2.
[0029] As the formwork for centrifugal molding, a general formwork for centrifugal molding (for example, a formwork for piles) can be used. A plurality of annular convex portions 2 (cass) are provided on the outer periphery of the mold frame 1 for centrifugal molding (hereinafter, simply referred to as the "mold frame") in Fig. 1. The annular convex portions 2 are annular convex portions provided along the outer periphery (surface) of the mold frame 1 for centrifugal molding in the short side direction. The number of annular convex portions 2 is not particularly limited and may be appropriately determined depending on the size of the mold frame 1 for centrifugal molding, but is usually 2 to 50, and preferably 3 to 30. Moreover, the environmental convex portions 2 are usually disposed at a specific interval that is arbitrarily determined. The mold 1 for centrifugal molding is placed on the upper part (upper part) of the vibration centrifugal molding machine 10. The vibration centrifugal molding machine 10 includes a rotating wheel 3 (runner wheel) for supporting the mold 1 for centrifugal molding, a vibration means 5 for applying vibration to the mold 1 for centrifugal molding, a rotation shaft C for rotating the rotating wheel, and a drive unit M for rotating the rotation shaft C. The rotating wheel 3 supports the centrifugal molding frame 1 at the vertical lower portion of the annular convex portion 2. The rotating wheel 3 has a shape that can fit into the annular convex portion 2, and the frictional conduction between the rotating wheel 3 and the annular convex portion 2 causes the centrifugal molding frame 1 to rotate about an axis that is the longitudinal direction of the centrifugal molding frame 1. The number of the rotating wheels 3 is not particularly limited and may be appropriately determined depending on the size of the mold 1 for centrifugal molding, but is usually the same as or less than the number of the environmental protrusions 2, preferably 2 to 50, and more preferably 3 to 30. Moreover, the rotating wheels 3 are usually disposed at a specific interval determined arbitrarily.
[0030] A vibration means 5 for applying vibration to the centrifugal molding frame 1 is disposed below the annular convex portion 2 in the vertical direction. The number of vibration means 5 is not particularly limited and may be appropriately determined depending on the size of the centrifugal molding frame 1, but is usually 1 or more, preferably 2 to 30, and more preferably 3 to 10. The vibration means 5 includes a rotatable gear-shaped member 5a for applying vertical vibration to the centrifugal molding frame 1 via the annular convex portion 2, and a pressing member 5c that supports the gear-shaped member 5a and can move the gear-shaped member 5a in the vertical direction. A plurality of convex portions (projections) are formed on the gear-shaped member 5a. The gear-shaped member 5a can be moved vertically upward by the pressing member 5c at any timing to press the annular convex portion 2. When the gear-shaped member 5a presses the annular convex portion 2, the gear-shaped member 5a also rotates in response to the rotation of the annular convex portion 2 accompanying the rotation of the mold for centrifugal molding 1, and the plurality of convex portions and concave portions (between the convex portions) formed on the gear-shaped member 5a come into alternate contact with the annular convex portion 2, thereby applying vibrations in the vertical direction (vertically upward and vertically downward) to the mold for centrifugal molding 1.
[0031] In the molding process, while rotating the centrifugal molding frame 1 around its longitudinal axis, vertical vibration is applied to the centrifugal molding frame 1 via the annular convex portion 2 using a vibration means 5 disposed in the vertical lower portion of at least one of the annular convex portions 2. The vibration is preferably applied while rotating the formwork 1 for centrifugal molding at a centrifugal acceleration of 10 G or less, more preferably 2 to 8 G, and particularly preferably 3 to 7 G. By applying vibration while rotating the formwork 1 for centrifugal molding at a centrifugal acceleration of 10 G or less, a gravitational acceleration of 100 to 2000 times the centrifugal acceleration generated during centrifugal molding is applied to the cement composition 4 in the formwork, and the formability of the cement composition can be further improved. From the viewpoint of further improving moldability and shortening the time required for centrifugal molding, centrifugal molding with and without vibration may be performed alternately. For example, centrifugal molding can be performed by repeating one cycle of rotating a mold frame 1 for centrifugal molding at a centrifugal acceleration of 4 to 6 G, vibrating the mold frame 1 for 20 to 40 seconds, and then rotating the mold frame 1 for centrifugal molding at a centrifugal acceleration of 12 to 18 G (preferably 14 to 16 G) for 20 to 40 seconds without vibration, with the cycle being repeated 1 to 5 (preferably 2 to 4) times. In order to further improve the moldability of the cement composition, after the above cycle, centrifugal molding may be performed at a centrifugal acceleration of 12 G or more (preferably 15 to 30 G, more preferably 18 to 25 G) without applying vibration, preferably for 120 to 420 seconds, more preferably for 180 to 360 seconds.
[0032] [Room temperature curing process] In this process, the uncured cylindrical molded body obtained in the molding process is subjected to sealed curing or air curing at 10 to 40°C for 20 hours or more, and then removed from the mold to obtain a cured cylindrical molded body. In this step, the curing temperature is 10 to 40° C., preferably 15 to 30° C. If the curing temperature is 10° C. or higher, the curing time can be shortened. If the curing temperature is 40° C. or lower, the strength of the concrete pile can be improved. The curing time is 20 hours or more, preferably 22 to 72 hours, and more preferably 24 to 48 hours. If the curing time is 20 hours or more, defects such as chipping and cracking are unlikely to occur in the hardened molded body when it is demolded. In this step, the cured cylindrical molded body preferably has a compressive strength of 20 to 100 N / mm 2 , more preferably 30 to 80N / mm 2 When the compressive strength of the molded body reaches 20 N / mm, the molded body is preferably removed from the mold. 2 If the compressive strength is 100 N / mm or more, defects such as chipping or cracking are unlikely to occur in the molded body when it is demolded. 2 If the above-mentioned range is not exceeded, the formed body can be made to absorb water with little effort in the water absorption step described below.
[0033] [Steam curing process] In this process, the hardened cylindrical molded body obtained in the previous process is steam cured at a temperature of 70° C. or higher but lower than 100° C. for 12 hours or more to obtain a cylindrical concrete pile. In this step, the curing temperature is 70° C. or higher and lower than 100° C., preferably 75 to 95° C., and more preferably 80 to 92° C. If the curing temperature is 70° C. or higher, the curing time can be shortened. If the curing temperature is lower than 100° C., the strength of the concrete pile can be improved. In this step, the curing time is 12 hours or more, preferably 24 to 96 hours, and more preferably 36 to 72 hours. If the curing time is 12 hours or more, the compressive strength of the cementitious hardened body can be improved.
[0034] [Water absorption process] A water absorbing step may be provided between the room temperature curing step and the steam curing step, in which the hardened cylindrical molded body obtained in the room temperature curing step is allowed to absorb water. As a method for making the hardened cylindrical molded body absorb water, a method of immersing the molded body in water can be mentioned. In addition, in the method of immersing the molded body in water, from the viewpoint of increasing the amount of water absorption in a short time and increasing the compressive strength of the concrete pile, (1) a method of immersing the molded body in water under reduced pressure, (2) a method of immersing the molded body in boiling water and then lowering the water temperature to 40°C or less while the molded body is still immersed, (3) a method of immersing the molded body in boiling water and then removing the molded body from the boiling water and then immersing the molded body in water at 40°C or less, (4) a method of immersing the molded body in water under pressure, or (5) a method of immersing the molded body in an aqueous solution in which an agent for improving the water permeability of the molded body is dissolved.
[0035] [High temperature heating process] After the steam curing step, a high-temperature heating step may be performed in which the hardened body (concrete pile) after steam curing is heated at 150 to 200°C (preferably 170 to 190°C) for 24 hours or more (preferably 24 to 72 hours, more preferably 36 to 48 hours). In this step, if the heating temperature is 150° C. or higher, the heating time can be shortened. If the heating temperature is 200° C. or lower, the compressive strength of the concrete pile can be improved. If the heating time is 24 hours or more, the compressive strength of the concrete pile can be improved.
[0036] The concrete pile obtained by the manufacturing method of the present invention has a compressive strength measured in accordance with "JIS A 1136:2018 (Method of testing compressive strength of centrifugally compacted concrete)" of preferably 175 N / mm 2 More preferably, 180N / mm 2 More preferably, 190N / mm 2 More preferably, 195 N / mm 2 The above compressive strength is 175N / mm 2 If this is the case, the thickness of the concrete pile can be maintained or reduced, and the tip bearing capacity coefficient α of the pile can be increased. Half of the value obtained by subtracting the inner diameter from the outer diameter of a concrete pile (thickness: (outer diameter-inner diameter) / 2) varies depending on the application of the concrete pile, but is preferably 30 to 300 mm, more preferably 35 to 200 mm, even more preferably 50 to 180 mm, and particularly preferably 70 to 140 mm. If the thickness is 30 mm or more, the tip bearing capacity coefficient α of the pile can be made larger. If the thickness is 300 mm or less, the amount of excavated surplus soil can be reduced when a bearing construction method is carried out using the pile. Furthermore, the weight of the pile can be reduced, thereby improving workability and reducing logistics costs. The outer diameter of the concrete pile varies depending on the application of the concrete pile, but is usually 150 to 3,000 mm, preferably 400 to 2,000 mm. EXAMPLES
[0037] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [Materials used] (1) Cement: Moderate heat Portland cement (manufactured by Taiheiyo Cement Corporation, density: 3.21 g / cm 3 ) (2) Slag gypsum admixture: density 2.64g / cm 3 , DC Company, product name "CeraPower CPSI" (3) Silica fume: BET specific surface area 20 m 2 / g (4) Inorganic powder: silica powder, 50% cumulative volumetric particle size 2 μm, maximum particle size 12 μm, 95% cumulative volumetric particle size 5.8 μm (5) Fine aggregate: crushed sand, maximum particle size 5.0 mm or less, surface dry density 2.62 g / cm 3 (6) Coarse aggregate A: crushed stone 1505, surface dry density 2.64g / cm 3 , crushing value 8%, maximum particle size 15mm (7) Coarse aggregate B: Crushed stone 2005, surface dry density 2.62 g / cm 3 , crushing value 8%, maximum particle size 20mm (8) High-performance water reducing agent: solid content 28.0% by mass, manufactured by Florick Co., Ltd., product name "Florick SF500U" (9) Defoamer: BASF Japan, product name "Master Air 404" (10) Water: Tap water The crushing value of the coarse aggregate was measured by the method described above.
[0038] [Examples 1 to 7] Cement, silica fume, inorganic powder, fine aggregate, and the types of coarse aggregate shown in Table 1 were all charged into a forced twin-shaft mixer and dry mixed for 30 seconds. The total volume of the charged materials, including cement, was set to 35 liters. Next, water, a high-performance water reducing agent, and an antifoaming agent were added to a forced twin-shaft mixer and mixed for 510 seconds. The amounts of cement, silica fume and inorganic powder were set so that, out of a total of 100 volume percent of the powder raw materials (cement, silica fume and inorganic powder), the proportion of cement was 60 volume percent, the proportion of silica fume was 14 volume percent, and the proportion of inorganic powder was 26 volume percent. The amounts of fine aggregate and coarse aggregate were determined so that the ratio of fine aggregate and coarse aggregate would be as shown in Table 1 in 100% by volume of the resulting cement composition. The amount of water was determined so that the mass ratio of water to the powdered raw materials would be the values shown in Table 1. Furthermore, the amount of high-performance water reducing agent (solid content equivalent) and the amount of defoaming agent were determined to be the amounts shown in Table 1 per 100 parts by mass of the powdered raw materials.
[0039] The kneaded cement composition was supplied to a cylindrical centrifugal molding mold with an inner diameter of φ200×300 mm. Next, the above mold was placed on a centrifugal molding machine, and the mold was rotated at a low speed with a centrifugal acceleration of 5 G, while the vibration means was operated (the gear-shaped member of the vibration means was moved vertically upward to press the annular convex portion), and centrifugal molding was performed for 30 seconds while applying vibration. Next, without applying vibration (the gear-shaped member of the vibration means was moved vertically downward to not press the annular convex portion), the mold was rotated at a medium speed with a centrifugal acceleration of 15 G for 30 seconds. After repeating 3 cycles of this low-speed rotation for 30 seconds and medium-speed rotation for 30 seconds as one cycle, molding was performed for 300 seconds while rotating the mold at a high speed so that a centrifugal force of 20 G was applied to the mold without applying vibration, to obtain an uncured molded body. The moldability in centrifugal molding was evaluated visually. Specifically, the uncured molded body was evaluated as follows: if the shape was kept cylindrical, the inner wall surface had no protruding aggregates, and the surface was smooth and had no uneven thickness (no variation in thickness), it was rated as "good"; if the inner wall surface had protruding aggregates, was not smooth, and had uneven thickness (variation in thickness), it was rated as "bad."
[0040] The uncured cylindrical molded body was then subjected to sealed curing at room temperature (about 20°C) for 24 hours, and then demolded to obtain a cured cylindrical molded body. The molded body was heated to a temperature shown in Table 1 at a heating rate of 20°C / hour, and then steam cured in an environment where the temperature was maintained for the time shown in Table 1 (shown as "steam curing step" in Table 1), to obtain a cylindrical concrete pile. The compressive strength of the above cylindrical concrete pile was measured in accordance with "JIS A 1136:2018 (Test method for compressive strength of centrifugally compacted concrete)". In addition, the overall evaluation of formability was "good" and the compressive strength was 175N / mm 2 More than 195N / mm 2 Those with a moldability rating of "good" and a compressive strength of 195N / mm 2 The above is rated as "◎", the moldability rating is "×", or the compressive strength is 175N / mm 2 Those with a value less than this were evaluated as "X". The thickness of the obtained cylindrical concrete pile was 40 mm. The results are shown in Table 1.
[0041] [Comparative Example 1] Cement, slag gypsum-based admixture, fine aggregate, and the types of coarse aggregate shown in Table 1 were all charged into a forced twin-axis mixer and dry mixed for 30 seconds. The total volume of the charged materials, including cement, was set to 35 liters. Next, water, a high-performance water reducing agent, and an antifoaming agent were charged into a forced twin-shaft mixer and mixed for 510 seconds to prepare a cement composition. The amounts of cement and slag gypsum-based admixture were determined so that the proportion of cement was 60 volume % and the proportion of slag gypsum-based admixture was 40 volume % out of a total of 100 volume % of the powder raw materials (cement and slag gypsum-based admixture). The amounts of fine aggregate and coarse aggregate were determined so that the ratio of fine aggregate and coarse aggregate would be as shown in Table 1 in 100% by volume of the resulting cement composition. The amount of water was determined so that the mass ratio of water to the powdered raw materials would be the values shown in Table 1. Furthermore, the amount of high-performance water reducing agent (solid content equivalent) and the amount of defoaming agent were determined to be the amounts shown in Table 1 per 100 parts by mass of the powdered raw materials. The cement composition after kneading was subjected to centrifugal molding in the same manner as in Example 1, but molding was not possible.
[0042] [Comparative Examples 2 to 6] A cement composition was prepared in the same manner as in Example 1, and then the mixed cement composition was used to carry out centrifugal molding in the same manner as in Example 1 to obtain an unhardened cylindrical molded body. Next, the unhardened cylindrical molded body was subjected to steam curing in the same manner as in Example 1 to obtain a cylindrical concrete pile. Evaluation of moldability in centrifugal molding was performed in the same manner as in the Examples. [Comparative Example 7] A cylindrical concrete pile was obtained in the same manner as in Example 2, except that no vibration was applied during centrifugal molding. Evaluation of moldability in centrifugal molding was performed in the same manner as in the Examples. The results are shown in Table 1.
[0043] [Table 1]
[0044] It can be seen from Table 1 that in Examples 1 to 7, cylindrical concrete piles having excellent moldability during centrifugal molding and high compressive strength were obtained. On the other hand, in Comparative Examples 2 to 3 (where the water / powder ratio was 0.10 or 0.17) and Comparative Examples 4 to 5 (where the coarse aggregate mixing ratio was 45 volume % or 10 volume %), it can be seen that the formability during centrifugal molding was poor and cylindrical concrete piles with low compressive strength were obtained. Also, it is understood that in Comparative Example 6 (steam curing time of 6 hours), a cylindrical concrete pile with low compressive strength was obtained. Furthermore, it is understood that in Comparative Example 7 (where no vibration was applied during centrifugal molding), the moldability during centrifugal molding was poor, and a cylindrical concrete pile with low compressive strength was obtained. [Explanation of symbols]
[0045] 1. Centrifugal molding formwork 2 Annular protrusion 3 Rotating Wheels 4. Cement composition 5. Vibration means 5a Gear-shaped member 5b Pressing member 10. Vibration centrifugal molding machine C Rotational Axis M Drive Unit
Claims
1. Cement and BET specific surface area of 15 to 25 m 2 a molding step of supplying a cement composition containing silica fume having a particle size of 0.8 to 5 μm, inorganic powder having a 50% cumulative particle size by volume of 0.8 to 5 μm, fine aggregate, coarse aggregate, a cement dispersant, and water to a form for centrifugal molding, and then centrifugally molding the cement composition while vibrating the form to obtain an unhardened cylindrical molded body; a room temperature curing step of subjecting the uncured cylindrical molded body to sealed curing or air curing at 10 to 40° C. for 20 hours or more, and then removing the uncured cylindrical molded body from the form to obtain a cured cylindrical molded body; a steam curing step of steam curing the hardened cylindrical molded body at 70° C. or higher but lower than 100° C. for 12 hours or more to obtain a cylindrical concrete pile; Including, In the cement composition, the proportion of the cement is 55 to 65 volume %, the proportion of the silica fume is 5 to 25 volume %, and the proportion of the inorganic powder is 15 to 35 volume %, based on a total amount of the cement, the silica fume, and the inorganic powder being 100 volume %, a mass ratio of the water to the total of the cement, the silica fume, and the inorganic powder (water / (total of the cement, the silica fume, and the inorganic powder)) is 0.11 to 0.16; A method for producing a cylindrical concrete pile, characterized in that the proportion of the coarse aggregate in the cement composition is 15 to 40 volume %.
2. The form has a plurality of annular protrusions provided on an outer periphery of the form, 2. A method for manufacturing a cylindrical concrete pile as described in claim 1, wherein, in the molding process, while the formwork is rotated around its longitudinal axis, vertical vibrations are applied to the formwork via the annular convex portion using a vibration means for applying vibration to the formwork, which is arranged at a vertical lower portion of at least one of the annular convex portions.
3. 3. The method for manufacturing a cylindrical concrete pile according to claim 2, wherein in the molding step, the formwork is vibrated while being rotated around an axis in the longitudinal direction of the formwork at a centrifugal acceleration of 10 G or less.
4. The method for manufacturing a cylindrical concrete pile according to claim 1 or 2, wherein the maximum particle size of the coarse aggregate is 10 to 25 mm.
5. The compressive strength of the cylindrical concrete pile measured in accordance with "JIS A 1136:2018 (Method for testing compressive strength of centrifugally compacted concrete)" is 175 N / mm 2 The method for manufacturing a cylindrical concrete pile according to claim 1 or 2.
6. The method for manufacturing a cylindrical concrete pile according to claim 1 or 2, wherein the cylindrical concrete pile has a thickness of 30 to 300 mm, half of the value obtained by subtracting the inner diameter from the outer diameter.
7. The method for manufacturing a cylindrical concrete pile according to claim 1 or 2, wherein the outer diameter of the cylindrical concrete pile is 150 to 3,000 mm.
Citation Information
Patent Citations
Manufacturing method of high-strength centrifugal molding concrete pipe
JP2013032246A
Stake and method for producing the same
JP2017095914A